Modeling pedestrian behavior with Cell-DEVS: theory and applications. (February 2016) - Al-Habashna, Ala'a; Wainer, Gabriel
In this work, we provide an approach for Modeling and Simulation (M&S) of crowds using Cellular Discrete EVent System Specification (Cell-DEVS). We present many examples of Cellular Discrete EVent System Specification entity-based crowd models, and we show how to use Cellular Discrete EVent System Specification for entity-based modeling and simulation of crowds. We provide an approach for using Cellular Discrete EVent System Specification theory in modeling and simulation of crowds, and we propose Cellular Discrete EVent System Specification entity-based models for modeling and simulation of one-, two-, and three-dimensional movement of crowds. We extend the models above, and propose a more advanced model for crowd movement in multi-level building. Furthermore, we use this model for simulation of building evacuations. We propose another advanced model for crowd modeling, and deploy the model in occupancy analysis of buildings. Simulation results verify the usability of the proposed models.